Situation map - Arkhangelsk / 29th Engineers, U.S. Army (United States. Army. Corps of Engineers. 29th Battalion (Base Topographic), 1919)
Includes legend.; Shows railroads, roads (2 classes), rivers, canals, marshes and swamps.; Stamped note at top left: "Exchange from Library of Congress Dec 1945". Color; 1:1,000,000